Fiscal Illusion Detection and Their Effect on Economic Growth in Sulawesi - Dody Hapsoro; Ryfal Yoduke (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
Abstract: The purpose of this study is to examine the existence of fiscal illusions in the form of flypaper effects and debt illusions in regional government spending and examine its effect on regional economic growth in Sulawesi. The number of samples is 78 based on the completeness criteria of data and information covered in the consolidated balance sheet of the Ministry of Finance of the Republic of Indonesia. The utilized analytical tool is partial least square analysis assisted by SmartPLS 3.0 software based on the Structural Equation Model (SEM). The results of the study show that there is a fiscal illusion in the form of flypaper effects and the illusion of debt in regional government expenditure. Furthermore, the results of the study show that the existence of fiscal illusions in regional government expenditure has a positive and significant effect on regional economic growth. Keywords: Fiscal illusion detection and economic growth.Keberadaan Ilusi Fiskal dan Pengaruhnya Terhadap Pertumbuhan Ekonomi di Sulawesi Abstrak: Tujuan penelitian ini adalah untuk menguji keberadaan ilusi fiskal dalam bentuk flypaper effect dan ilusi hutang dalam belanja pemerintah daerah dan menguji pengaruh ilusi fiskal terhadap pertumbuhan ekonomi daerah di Sulawesi. Jumlah sampel adalah sebanyak 78 berdasarkan kriteria kelengkapan data dan informasi yang terdapat dalam neraca gabungan Kementerian Keuangan Republik Indonesia. Alat analisis yang digunakan adalah analisis parsial kuadrat terkecil dengan bantuan perangkat lunak SmartPLS 3.0 berdasarkan Structural Equation Model (SEM). Hasil penelitian menunjukkan bahwa ada ilusi fiskal dalam bentuk flypaper effect dan ilusi hutang pada belanja pemerintah daerah. Hasil penelitian selanjutnya menunjukkan bahwa keberadaan ilusi fiskal pada belanja pemerintah daerah berdampak positif dan signifikan terhadap pertumbuhan ekonomi daerah. Kata kunci: Deteksi ilusi fiskal dan pertumbuhan ekonomi.